Optimalisasi Dalam Meningkatkan Keaktifan Jama’ah Melalui Program Tematik Berbasis Masjid Al Muhajirin di Desa Kungkai Baru - Sopia, Gebby; Nadia Pransista; Debi; Meliza Tri Aprilia; Anggun Febiola; Dini Putri Pebriani; Danang Prabowo; Intan Purnama; Rensa Eca Febria (MENYALA: Jurnal Pengabdian Masyarakat, 2024)
Community Service Program (KKN) is a crucial component of the academic curriculum, providing students with the opportunity to engage directly with the community, apply their knowledge, and positively contribute to community development. The KKN program in Desa Kungkai Baru focuses on developing Masjid Al Muhajirin as a center for religious and social activities with the goal of enhancing the engagement of congregants through a mosque-based thematic approach. This program aims to strengthen social and spiritual bonds within the community through relevant religious, educational, and social activities. The Asset-Based Community-Driven Development (ABCD) approach is utilized to leverage local strengths in designing and implementing the program. The evaluation results show that students play a key role in designing, implementing, and motivating congregant participation. However, challenges such as community resistance and resource limitations need to be addressed with creative solutions. The conclusion outlines the students’ contributions, the program’s effectiveness, and its impact on community empowerment while providing recommendations for future improvements in the KKN program.